Research Paper on Development Programs on Education in India: Exploring the Impact of Development Programs on Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Sarva Shiksha Abhiyan is the main program and basically aims to provide quality education to all. Training was considered the most powerful means of empowerment. It should reach the doors of the poor, the economically disabled and the socially depressed. In addition, infrastructure facilities have a positive role in the development of primary education. The objective of developing infrastructure in primary education is to increase the attendance rate and increase the academic performance of students